2021
DOI: 10.36834/cmej.72081
|View full text |Cite
|
Sign up to set email alerts
|

The “virtual OR:” creation of a surgical video-based gynaecologic surgery teaching session to improve medical student orientation and supplement surgical learning during COVID-19

Abstract: Implication Statement The COVID-19 pandemic resulted in changes to clinical clerkship delivery including decreased surgical exposure. The Department of Obstetrics and Gynaecology at Dalhousie University developed a novel, resident-led learning experience using a curated presentation of operative footage. This session aimed to improve medical students’ orientation to the operative environment and supplement teaching on pelvic anatomy and gynaecologic surgery in response to decreased exposure during the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Nearly all students agreed that the videos helped learning about gynecological surgery and that it should be shown to all students at the start of their rotation. 22 It has been shown that students were interested in using surgical videos as resources for studying surgical anatomy. The group given access to surgical videos had self-reported improvement in surgical knowledge as well as objectively improved knowledge scores.…”
Section: Macdonald Et Almentioning
confidence: 99%
“…Nearly all students agreed that the videos helped learning about gynecological surgery and that it should be shown to all students at the start of their rotation. 22 It has been shown that students were interested in using surgical videos as resources for studying surgical anatomy. The group given access to surgical videos had self-reported improvement in surgical knowledge as well as objectively improved knowledge scores.…”
Section: Macdonald Et Almentioning
confidence: 99%
“…Augmentation of medical education with VR technology has demonstrated established benefits, from factual and spatial knowledge acquisition to improvements in technical skills and applications in anatomy. [7][8][9] It provides immersion in interactive settings with the autonomy to explore and apply clinical knowledge for flexible remote learning, thereby creating engaging opportunities for education from virtually anywhere across the globe! As demonstrated in this pilot project, our ICE application has not only allowed medical students to continue clinical experiences under restrictions of the COVID-19 pandemic, but it also created a truly standardized patient encounter thereby enabling all students a fair and equitable learning opportunity.…”
Section: Next Stepsmentioning
confidence: 99%